1971
DOI: 10.1111/j.1432-1033.1971.tb01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bile Acids on the Activity of Rat Liver 3‐Hydroxy‐3‐methylglutaryl Coenzyme A Reductase

Abstract: 1.Cholic acid feeding strongly depresses the activity of the rate limiting enzyme of cholesterol synthesis in liver 3-hydroxy-3-methylglutaryl CoA reductase. Experiments were undertaken to decide between (a) a direct influence of the bile acid itself in liver or (b) an indirect effect of the bile acid by improving the intestinal resorption of cholesterol, which itself then would depress the activity of hepatic 3-hydroxy-3-methylglutaryl CoA reductase.2. For this purpose lymph fistula rats were fed with cholic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1973
1973
1997
1997

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…* Values that differ from the control values (group B) at the P c 0.05 level. (24). To obtain more definitive data in this critical group of animals, 24 more rats were prepared with intestinal lymphatic cannulae, and half of these were infused with taurocholate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…* Values that differ from the control values (group B) at the P c 0.05 level. (24). To obtain more definitive data in this critical group of animals, 24 more rats were prepared with intestinal lymphatic cannulae, and half of these were infused with taurocholate.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier work we found no evidence that bile acids have a direct regulatory effect upon the rate-limiting enzyme, 8-hydroxy-,B-methylglutaryl-CoA reductase (HMG CoA reductase),' in the cholesterol bio-synthetic pathway and suggested that the principal effect of bile acid was to modulate the amount of cholesterol absorbed from the gastrointestinal tract (23). Subsequent work, however, has demonstrated that cholesterol synthesis in the liver is suppressed by bile acid feeding under circumstances where cholesterol absorption is partially, or perhaps completely, blocked by the administration of 8-sitosterol (20) or by intestinal lymphatic diversion (24). Alternatively, hepatic cholesterol synthesis has been found to be enhanced after resection of the terminal ileum under circumstances where cholesterol absorption apparently is unchanged (25).…”
mentioning
confidence: 99%
“…Hamprecht et al (28) diverted the lymph and hence any absorption of cholesterol, and fed bile salts to these rats. They found that cholic acid feeding under these circumstances was effective in reducing the level of hepatic H1MG CoA reductase.…”
Section: A D Coopermentioning
confidence: 99%
“…Possibly other stimuli affecting liver 3-hydroxy-3-methylglutaryl-CoA reductase, such as starvation (Linn, 1967;Hamprecht et al, 1969), dietary bile acids (Hamprecht et al, 1971) and other dietary components (Craigetal., 1972), do so non-specifically. At any rate, a test, such as that described in the …”
Section: Resultsmentioning
confidence: 99%